Answer:
x = 4 ±√26
Step-by-step explanation:
Please write this as x^2 - 8x = 10, or x^2 - 8x - 10 = 0. " ^ " indicates exponentiation.
Let's complete the square:
x^2 - 8 x can be rewritten as
x^2 - 8x + 16 - 16, and so
x^2 - 8x = 10 becomes x^2 - 8x + 16 - 16 - 10 = 0, or
(x - 4)^2 = 26
Taking the square root of both sides, we get:
x - 4 = ±√26, or
x = 4 ±√26
Answer:
since the ratio of y to x (also written y:x) never changes. The number 6 in the equation yx=6 y x = 6 is called the constant of variation. The equation yx=6 y x = 6 can also be written in the equivalent form, y=6x y = 6 x .
Step-by-step explanation:
The answer is True
Answer:
-<u>One Equation</u>: is set equal to a variable
Example:
y = 2x + 1
x + 3y = -12
You already have y, plug it back into x + 3y = -12
x + 3(2x + 1) = -12
x + 6x + 3 = -12
7x + 3 = -12
(Subtract 3 from each side)
7x = -15
(Divide by 7)
x = - 2.14
-<u>No Equation</u>: is set equal to a variable
Example:
2x + y = 10
4× + 2y = -3
Subtract 2x from each side of 2x + y = 10, you should get y= -2x + 10. Now that you have found y, substitute y into 4x+ 2y = -3.
4x + 2(-2x + 10) = -3
4x + -4x + 20 = -3
(Subtract 20 from each side)
4x + -4x = -23
(Add 4x and -4x)
0 = -23
No Solution
<u>-Both</u><u> </u><u>Equations</u>: are set equal to a variable
Example:
y = x + 5
y = -x + 3
(you already have y so plug it into the other equation to solve for x)
-x + 3 = x + 5
(Add -x on both sides)
3 = 2x + 5
(subtract 5 from both sides)
-2 = 2x
(Divide by 2 on each side)
x = -1
I hope this helped!
A) the null hypothesis is incorrectly accepted when it is false